Konsentrasi Spermatozoa Burung Parkit (Melopsittacusundulatus) pada Berbagai Frekuensi Penampungan - - Nurkolis (Politeknik Negeri Jember, 2017)
This study was conducted from 6 to 12 November 2000 in Reproduction Laboratory of Animal Husbandry Faculty. The purpose of this study was to know difference of parakeet spermatozoa concentration in variation of collecting frequency level. The result is hoped useful in giving information about collecting frequency level hold for a week. The material use were 3 adult male parakeet took their semen during a week for three times collection by interval to days. The method was complete randomized design. The treatments were comparing spermatozoa concentration of the adult male parakeet in variation of collecting frequency level. The data obtained were analyzed by Duncan Multiple Range Test (DMRT). The result of study showed that spermatozoa spermatozoa concentration rate of different level for the first, second, and third frequency was 81,33 ± 5,35 107/ml; 70,33 ± 7,32 107/ml; and 43,33 ± 5,35 107/ml respectively. There was significant different effect (P<0,01) in collection frequency level on the spermatozoa concentration. The result of DMRT showed that the fist and second collecting was similar but unsimilar to the third. The conclusion of this study was the collecting frequency gives significant effect (P<0,01) on the spermatozoa concentration of the parakeet. The first and second collecting has no significant effect on the spermatozoa concentration, so that it is considerable that the optimal number of collecting for the semen of the parakeet was twice a week.